PENGARUH SERVICE DELIVERY TERHADAP KEPUASAN WISATAWAN DALAM MENGGUNAKAN PAKET OUTBOUND DI OBJEK WISATA LINGGARJATI INDAH KABUPATEN KUNINGAN (Survey pada Wisatawan yang Menggunakan Paket Outbound di Objek Wisata Linggarjati Indah Kabupaten Kuningan) - Asih, Mega Tresna; Malihah, Elly (Universitas Pendidikan Indonesia, 2013)
Tourism is one sector of the economy that grew into the industry that provides income benefits for a country in the world. Development and construction of the tourism sector should be used as revenue by developing the existing potential of such natural beauty and culture with the aim of attracting tourists who could be known by foreign tourists. Kuningan district is one of tourist destination that has many attractions of heritage sites in earlier times that have historical value to the District of Kuningan. In addition to review of its history, District of Kuningan is an area that could be developed as a tourism object. Not far from the building of Linggarjati conference, there are available the natural attractions to complement the tourist area of Linggarjati building conference. The place is called Linggarjati Indah. The administrator of Linggarjati Indah of Kuningan District focuses on improving traveler satisfaction through a system of service delivery. Customer satisfaction will be filled if the process of delivering services from providers to consumers in accordance with what is perceived by tourists. This study aims to determine the picture of service delivery, picture of the level of tourist satisfaction and service delivery impact on tourist satisfaction. The object in this study is, that tourists are using outbound package of Linggarjati Indah of Kuningan District. The independent variable in this study is the service delivery (X). And the dependent variable in this study is the satisfaction of tourists (Y). This research uses descriptive and verified method, by the method of explanatory survey. The data analysis technique, the writer uses the technique of multiple regression analysis with SPSS 18.0 program for windows. The results showed that variables of service delivery service facilities, personnel, roles and scripts simultaneously affect the satisfaction of tourists who use the outbound package at Linggarjati Indah of Kuningan District. Whereas only partial personnel and roles that significantly influence tourist satisfaction.